Skin lesions serve as clues to relapse of pediatric blastic plasmacytoid dendritic cell neoplasm. Issue 2 (13th February 2018) - Dreyer, Sean; Mednik, Suzanne; Truong, Allison; Worswick, Scott; Scumpia, Philip; Neill, Daniel; Kannan, Swati; Hogeling, Marcia
Abstract: A 10‐year‐old girl with a history of blastic plasmacytoid dendritic cell neoplasm, a rare malignancy in children, presented with recurrent skin eruptions beginning while on maintenance chemotherapy, including mildly pruritic skin‐colored plaques, tender indurated nodules, and violaceous bound‐down plaques. This case highlights an unusual presentation of relapsed blastic plasmacytoid dendritic cell neoplasm on chemotherapy, with skin lesions providing important clues to the progression of systemic disease.